A política de fundo público para o financiamento da Educação Básica: impacto e impasses no município de Fortaleza - Sousa, Antonia de Abreu (2009)
The policy of funding education in recent times has decreased significantly. The reflex of this situation are the mechanisms used by The Federal Government, which had direct intervention by cutting the public funds in the revenue related to education, such as the untying with the DRU, the priority of only one level of education, the elementary, from seven to fourteens years old, and the expansion of high school at low cost. To realize these actions, an accounting institute, FUNDEF, was created just to finance basic education, established in 1996 running until 2006. The organizations committed to education, however, pressured for the establishment of a fund covering all levels of basic education, evidencing struggle for the fund resources. In 2006, FUNDEB was created, institutionalizing in Brazil the specific funds for financing the education. On the subject, we analyze the current financing of basic education with the public funds, its reflex on the policies for enhancement of teaching highlighting the impact of these funds and the impasses in the city of Fortaleza. It follows that, in the city of Fortaleza, the FUNDEF, despite some progress, has not changed the history of finance. There was no increase in the cost/ student a year, but decrease, contributing to this the accelerated municipalization of education, which has not been accompanied by more resources, and the existing ones were not enough to offer quality education for all. This situation also occurs with FUNDEB, which, despite bringing redistributive effects, with incentives and reduction of inequalities of care depending on the factors of distribution set for different segments of education, is not evidence of resources to increase the cost/student.